2018
DOI: 10.1124/mol.117.111443
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Substrate-Dependent Ligand Interactions at the Organic Cation Transporter OCT2 Using Six Model Substrates

Abstract: Organic cation transporter (OCT) 2 mediates the entry step for organic cation secretion by renal proximal tubule cells and is a site of unwanted drug-drug interactions (DDIs). But reliance on decision tree-based predictions of DDIs at OCT2 that depend on IC values can be suspect because they can be influenced by choice of transported substrate; for example, IC values for the inhibition of metformin versus MPP transport can vary by 5- to 10-fold. However, it is not clear whether the substrate dependence of a li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
84
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3
1

Relationship

3
6

Authors

Journals

citations
Cited by 81 publications
(88 citation statements)
references
References 38 publications
3
84
0
1
Order By: Relevance
“…The Assay Central software has been previously described (23)(24)(25)(26)(27)(28)(29)(30)(31)(32) which uses the source code management system Git to gather and store structure-activity datasets collated in Molecular Notebook (Molecular Materials Informatics, Inc. in Montreal, Canada). The output is a high-quality dataset and a Bayesian model using extendedconnectivity fingerprints of maximum diameter 6 (ECFP6) descriptors.…”
Section: Lysosomotropic Machine Learning Modelmentioning
confidence: 99%
“…The Assay Central software has been previously described (23)(24)(25)(26)(27)(28)(29)(30)(31)(32) which uses the source code management system Git to gather and store structure-activity datasets collated in Molecular Notebook (Molecular Materials Informatics, Inc. in Montreal, Canada). The output is a high-quality dataset and a Bayesian model using extendedconnectivity fingerprints of maximum diameter 6 (ECFP6) descriptors.…”
Section: Lysosomotropic Machine Learning Modelmentioning
confidence: 99%
“…Currently, novel molecular entities (NMEs) are tested for interaction with hOCT1 and hOCT2 expressed in epithelial cells to determine whether they inhibit uptake of a cationic model substrate that is applied at a micromolar concentration (Ahlin et al, 2008(Ahlin et al, , 2011Chen et al, 2017). This procedure has turned out to be insufficient because it was observed that the efficacy of inhibitors was dependent on the molecular structure of the employed substrate and was different when substrate concentrations far below their respective Michaelis-Menten constant (K m ) values were used for uptake measurements (Belzer et al, 2013;Thévenod et al, 2013;Yin et al, 2016;Minuesa et al, 2017;Gorboulev et al, 2018;Sandoval et al, 2018). For example, high-affinity inhibition of uptake of 1-methyl-4-phenylpyridinium 1 (MPP 1 ) by hOCT1, hOCT2, and human OCT3 (hOCT3) by the nucleoside reverse transcriptase inhibitor tenofovir disoproxil fumarate was observed when uptake was measured with 12.5 nM MPP 1 but did not show up when uptake was performed with 1 mM MPP 1 (Minuesa et al, 2009(Minuesa et al, , 2017.…”
Section: Introductionmentioning
confidence: 99%
“…Machine learning models for chordoma drug discovery. Several recently published studies of compounds screened against chordoma cell lines 20,21 were used to generate Bayesian machine learning models with our Assay Central software 10,12,[22][23][24][25][26][27][28][29] . In one published chordoma study 1097 compounds were screened against 3 chordoma cell lines (U-CH1, U-CH2, MUG-Chor1) and 27 had chordoma selective cytotoxicity 20 and many of these were EGFR inhibitors.…”
Section: Resultsmentioning
confidence: 99%
“…These datasets underwent curation to remove problematic molecules before model building as described elsewhere 10,12,[22][23][24][25][26][27][28][29] . We utilized Assay Central which has been previously described in detail 10,12,[22][23][24][25][26][27][28][29] to prepare and merge datasets collated in Molecular Notebook 60 , as well as generate Bayesian models using ECFP6 descriptors 61,62 . Briefly, the Assay Central project includes automated workflows for curating well-defined structure-activity datasets that employ a set of rules for the detection of problematic data (i.e.…”
Section: Model Namementioning
confidence: 99%